Geomorphological Characteristics of Denudational Landforms in Cibalong, Tasikmalaya Regency, West Java, Indonesia - Muhammad Fachri Aditya Putra; Edy Sutriyono; Ugi Kurnia Gusti (MO.RI Publishing, 2026)
The Cibalong area, Tasikmalaya Regency, West Java, is dominated by denudational landforms developed on volcaniclastic and clastic rocks of the Jampang and Bentang Formations. However, systematic geomorphological documentation of denudational landforms in this area remains limited, particularly regarding the relationship between lithology, slope characteristics, drainage patterns, and active denudational processes at a 1:25,000 mapping scale. This study aims to analyze the geomorphological characteristics of denudational landforms and their relationship with lithological units in the study area. The methods used include interpretation of DEMNAS data with a spatial resolution of approximately 8.1 m, processed using ArcGIS 10.8, combined with morphographic and morphometric analysis, drainage pattern analysis, and field verification to identify relief, slope gradient, lithology, and active geomorphic processes. The results show that the Cibalong area is dominated by Low Denudational Hills and Denudational Hills units. Slope classes of 15–30% and 30–70% dominate the study area, indicating undulating to hilly relief. Denudational landforms mainly develop on tuff of the Jampang Formation and tuffaceous sandstone, sandstone, and claystone of the Bentang Formation, which are relatively susceptible to weathering and erosion. The sub-parallel drainage pattern and the presence of rotational slides indicate that denudational processes remain active. Therefore, the geomorphology of Cibalong is mainly controlled by lithological characteristics, slope morphometry, drainage development, and the intensity of denudational processes. These findings provide scientific insight into denudational landscape development in the Southern Mountains of West Java and offer practical baseline information for geomorphological mapping, slope hazard assessment, and land-use planning in similar hilly terrains.